Can two-dimensional video analysis during single-leg drop vertical jumps help identify non-contact knee injury risk? A one-year prospective study. Issue 8 (October 2015) - Dingenen, Bart; Malfait, Bart; Nijs, Stefaan; Peers, Koen H.E.; Vereecken, Styn; Verschueren, Sabine M.P.; Staes, Filip F.
Abstract Background Previous studies showed that the amount of hip flexion and the combination of knee valgus and lateral trunk motion, measured with two-dimensional video analysis, were related to three-dimensional measured knee joint moments during single-leg drop vertical jumps, but it remains unclear whether these measurements can be used to identify non-contact knee injury risk. Methods Fifty injury-free female athletes participated in the study. Two-dimensional video analysis was used to measure hip flexion, knee valgus and lateral trunk motion angles during single-leg drop vertical jumps. Time loss non-contact knee injuries were registered during a one-year follow-up. Independent t-tests and receiver operating characteristic analysis were used to analyze the predictive ability of the two-dimensional angles. Findings Seven participants sustained a time loss non-contact knee injury. Hip flexion was not significantly different between groups (P > .05). The combination of knee valgus and lateral trunk motion was significantly smaller in the injured (P = .036) and non-injured legs (P = .009) of the future injured group compared with the respective matched leg of the non-injured group. The receiver operating characteristic analysis showed a significant discriminative accuracy between groups for the combination of knee valgus and lateral trunk motion of the uninjured leg of the future injured group with the matched leg of the non-injured group (area under curve = 0.803; P = .012). Interpretation The measurement of a combination of increased knee valgus and ipsilateral trunk motion during the single-leg drop vertical jump with two-dimensional video analysis can be used to help identify female athletes with increased non-contact knee injury risk.